Android mobile 3D augmented reality engineering devices design using marker-based technique - Mohamad Azim Ibrahim; Murizah Kassim; Jasni Mohammad Zain; Suhaili Beeran Kutty; Marina Mohd Yusoff; Barokah Isdaryanti; Farid Ahmadi; Nor Syazwani Mohd Pakhrudin (Institute of Advanced Engineering and Science, 2026)
Engineering teaching and learning utilizing using augmented reality (AR) technologies is crucial with new technology adaptation. This study has developed an Android mobile based augmented reality of engineering device (ARED) with description using marker-based technique. Unity 3D, Vuforia, and Blender Animation were used to design 3D models of engineering devices on AR platforms. ARED is used to scan a marker and display an AR 3D model of engineering devices with its information. Ten engineering devices models were created using Blender Animation Tools and exported to Unity 3D which are Ups Power, Infrared Thermometer, Cisco Router, Multi meter, Poe Switch, Clamp Meter, Power Supply, Arduino Uno, Raspberry Pi and Oscilloscope. ARED mobile app is successfully tested which presents users can interact with the 3D model using touch input to enhance their learning experience. Result presents user’s evaluation analysis at 86.2% of ARED’s effectiveness and impact for future education. The technical analysis shows that ARED can handle the optimum distance range between 35 to 100 cm, operation angle is best between 45 and 135 degrees and occlusion average maximum of 55%. The significance of the research is to improve the quality and process of engineering education by using AR and promotes the learning society’s transition to digital learning with mixed reality in engineering, which creates a borderless learning environment.